2021
DOI: 10.1021/acsmaterialslett.0c00550
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots (GQDs) for Bioimaging and Drug Delivery Applications: A Review

Abstract: Quantum dots (QDs) exhibit unique physicochemical and optical properties that are suitable for photovoltaic cells, light-emitting diodes, and optoelectronic devices; however, unlike selenium and tellurium/metalsulfide-based QDs, graphene quantum dots (GQDs) are comparatively less toxic and biocompatible, making them promising candidates for biological applications such as bioimaging, drug delivery agents, therapeutics, and theranostics. Various synthesis techniques such as top-down and bottom-up methods along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(71 citation statements)
references
References 139 publications
0
64
0
Order By: Relevance
“…The EDAX study proved that the as-synthesized MoS2 nanostructure comprises Mo and S elements, including oxygen atoms. Further, no other elements were found, which verified the purity of as-prepared samples [ 1 , 12 , 32 ].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The EDAX study proved that the as-synthesized MoS2 nanostructure comprises Mo and S elements, including oxygen atoms. Further, no other elements were found, which verified the purity of as-prepared samples [ 1 , 12 , 32 ].…”
Section: Resultsmentioning
confidence: 72%
“…MoS 2 nanocrystals can be used in many biomedical applications because of their tunable size and adequate luminescence properties. It has been widely applied in medicine, drug delivery, diagnostics, and outstanding biocompatibility in living organisms [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The excellent biocompatibility of CQDs is due to their small size and surface groups, 88 as well as biocompatibility of precursors, distribution of the surface charges and even the structural properties of carbon elements. [89][90][91] The particle size of CQDs is generally less than 10 nm, which makes it impossible to observe through ordinary optical microscopy.…”
Section: Characterization and Biocompatibility Of Cqdsmentioning
confidence: 99%
“…Additionally, we showed that GQDs exhibit low cytotoxicity and do not affect microbiome environment when fed to mice via oral administration [39]. GQDs also can be loaded with various drug molecules and genes through physicochemical conjugation between their functional groups [40][41][42][43][44]. Like GOs, GQDs need additional functionalization to interact electrostatically or covalently with therapeutic molecules or genes [45,46].…”
Section: Introductionmentioning
confidence: 99%